European Architectural History Network - European Architectural History Network (2007)
[Dt.:] Die Website des European Architectural History Network (EAHN) bietet über eine Datenbank Informationen zu Veranstaltungen im Bereich der europäischen Architekturgeschichte: Konferenzen, Vorträge, Ausstellungen, Call for Papers, Studienreisen, Zuschüsse und Stipendien. [Engl.:] The European Architectural History Network (EAHN) presents listings of current and previous events related to architectural history in a searchable database: conferences, lectures, exhibitions, calls for papers, study tours, grants and fellowships.